Pengenalan Metode Pembayaran Cash On Delivery (COD) Dalam Kegiatan Transaksi Belanja Online Pada Warga Dusun II Desa Sidoluhur - Suhardi, Mutia Aprizki; Febliansa, M. Rahman; Anzori, Anzori; Damarsiwi, Eska Prima Monique (Jurnal Dehasen Mengabdi, 2023)
Most people often make payments using the Cash On Delivery method, but there are still many who don't know what Cash On Delivery really means. Some people are more familiar with the acronym than the practice of Cash On Delivery itself, blaming the courier as the party responsible for the shortage or error of the goods they ordered. Sidoluhur village is located in Sukaraja district, Seluma district, Bengkulu province. Many residents in Hamlet II of Sidoluhur Village still do not understand this problem. Therefore, efforts that can be made are by conducting an introduction which on this occasion is packaged in the form of a PKM activity with the title "Introduction to Cash On Delivery (COD) Payment Methods in Online Shopping Transaction Activities". The method used is in the form of lectures with presentation of material, then a practical method with its application on one of the online shopping sites on each of the residents' gadgets, and followed by a discussion session with residents who actively ask questions to obtain information. So by holding an introduction to residents in Dusun II Sidoluhur Village, they prefer the Cash On Delivery payment method with various conveniences, one of which is without having to leave the house. Thus the percentage of online purchases will increase.